A review on the legal rights of indigenous people in Peninsular Malaysia: A comparative study with Australia and New Zealand / Zarith Zahirah Mohd Zakaria … [et al.] - Mohd Zakaria, Zarith Zahirah; Mohd Noor, Norsuriati; Jernus, Qiu Aqilah; Abdullah, Norhafizah (Faculty of Law, 2013)
This research study consists of all chapters on our research background, status and rights of Orang Asli in Malaysia, New Zealand, and Australia. The purpose of this study is to analyse every law that enshrined the provisions regarding aboriginal peoples in Malaysia, New Zealand and Australia. Then, we compare the law in Malaysia with the law in New Zealand and Australia. Moreover, this study is important as to ensure that all Orang Asli's rights in Peninsular Malaysia would be protected under the law. This research also highlights the importance of the revolution and reformation in shaping the actions of the Malaysian government.